Students’ Perceptions of Using Digital Product in English Class Activities at SMAN 3 Pekanbaru - chairunisa suci; destina kasriyati (Universitas Lancang Kuning, 2021)
Digital products is a learning media, when learning at home become one of choice learning now. The aim of this study at investigiting students' perceptions of using digital products in learning at SMAN3 Pekanbaru. This study was a survey research conducted from March to April 2021 in grade 11. The questionnaire was used as the main instrument for collecting data. Data analysis was performed by categorizing student responses to each questionnaire question into graphs. The data was analyzed based on the responded